Recent advances in (patho)physiology of astroglia - Verkhratsky Alexei; Parpura Vladimir (Acta Pharmacologica Sinica; Vol 31, No 9 (September 2010): Acta Pharmacologica Sinica(Special Feature:Celebrating the 30th Anniversary of APS）, 2016)
Our view of astrocytes in the operation of the brain is changing dramatically over the last 3 decades. Astroglial calcium excitability controls the release of gliotransmitters, which can occur at the tripartite synapse. Astrocytes not only modulate synaptic transmission by releasing and taking up transmitters, but also receiving neuronal signals that act upon astrocytic plasma membrane receptors. This process represents the bidirectional neurone-glia communication. Additionally, astrocytes play role in the regulation of blood flow as well as ion and water homeostasis. Many of the brain dysfunctions are primary astropathies, including hepatic encephalopathy and Alexander disease, while other brain malfunctions, such as epilepsy and Alzheimer disease, may have substantial astrocytic contribution. Thus, these star-shaped cells by their roles in (patho)physiology of the brain seem to live up to the expectation one can have from their given name – astrocyte.